PENITI SEBAGAI SIMBOL KEHIDUPAN DALAM KARYA SENI LUKIS - HARI FIRMANSYAH, Yofita Sandra, S.Pd, M.Pd, Drs. H. Achyar Sikumbang (Serupa The Journal of Art Education, 2014)
Safety-pin as a sharp thing has function in daily life. If we see from visual side small craft object has a abstract or unique shape however it has many benefit and function as a connector and unifier in the paint with tittle “Peniti Sebagai Simbol Kehidupan dalam Karya Seni Lukis”.Safety-pin is something to connecting two object which want to connected each other. In the daily life, we have many problem in culture and balancing of environment. Precisely, safety-pin as a symbol to unifier in life.In this final project, author focus on culture, nature and the safety-pin as a main object. Safety-pin is presented in surrealiesm by ignoring form of safety-pin. Then, authorturn every part from the object to make sensation which can understand by everybody. The word of art entittled 1). Belum Simbang; 2). Rumah Kita; 3). Mencoba Melindungi; 4). Grafik Naik; 5). Masih di Awan; 6). Terlahir Kembali; 7). Alam ku Ini; 8). Kedamaian; 9). Yang Tersisa dan 10). Merasakan Keindahan. All of those art presented many kind as a symbol of daily life.In conclusion, all of the word of art, safety-pin has important role in daily life, it become a connector in life contradiction , like a culture or balance of environment. In other way, it can be educational process to authoror societ who care about culture and environment.Key word: Safety-pin, symbol of life in paintin